Hair hygiene associated with female students' pediculosis capitis at a boarding secondary school - Mohammad Farhan Maulana; Yudha Nurdian; Bagus Hermansyah; Nurfaizah Titisari Sulihah (KHD-Production, 2026)
Pediculosis capitis is an infestation of the ectoparasite Pediculus humanus var. capitis on the hair and scalp, which remains a public health issue with a high prevalence, particularly among school-aged children and adolescents. Islamic boarding schools are highly vulnerable to transmission due to communal living patterns and the frequent sharing of personal items. This study aimed to determine the relationship between hair hygiene knowledge and the occurrence of Pediculosis capitis among female students. An observational-analytic, cross-sectional study was conducted with 52 respondents selected according to inclusion and exclusion criteria. Data were collected through microscopic examination of hair lice samples. The results revealed a significant relationship between hair hygiene knowledge and Pediculosis capitis infestation. The students’ knowledge and hair hygiene practices were relatively low, as reflected by the high prevalence rate of infestation (72.5%). Therefore, increasing health education and promotion regarding hair hygiene in boarding schools is essential as a preventive strategy against Pediculosis capitis.